Rol' i uchastie mestnykh organov vlasti Germanii i Frantsii v razvitii fizicheskogo vospitaniya i sporta - Sokolov, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this paper is to show the role and participation of local authorities in Germany and France in physical education and sport's development. The authors analyze the main directions and aspects of german and franch local authorities' activities in the area of physical education, physical culture and sport.